2023
DOI: 10.28991/esj-2023-07-04-013
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Fusion algorithms for Detecting Land Surface Pattern Changes Using Multi-High Spatial Resolution Images and Remote Sensing Analysis

Abstract: Producing accurate Land-Use and Land-Cover (LU/LC) maps using low-spatial-resolution images is a difficult task. Pan-sharpening is crucial for estimating LU/LC patterns. This study aimed to identify the most precise procedure for estimating LU/LC by adopting two fusion approaches, namely Color Normalized Brovey (BM) and Gram-Schmidt Spectral Sharpening (GS), on high-spatial-resolution Multi-sensor and Multi-spectral images, such as (1) the Unmanned Aerial Vehicle (UAV) system, (2) the WorldView-2 satellite sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Similar results can be found in [25]. Yang et al [26] revealed that the SWAP index, combined with the multi-threshold run theory enables a more accurate identification of DFAA events in the Yangtze River basin [27][28][29]. The study found that the SPI and SPEI have strong monitoring ability for drought in the southern part of northern China.…”
Section: Introductionsupporting
confidence: 74%
“…Similar results can be found in [25]. Yang et al [26] revealed that the SWAP index, combined with the multi-threshold run theory enables a more accurate identification of DFAA events in the Yangtze River basin [27][28][29]. The study found that the SPI and SPEI have strong monitoring ability for drought in the southern part of northern China.…”
Section: Introductionsupporting
confidence: 74%
“…In this study, Landsat images of Thematic Mapper (TM), Enhanced Thematic Mapper (ETM), and Landsat 8-Operational Land Images (OLI) (Dibs et al 2023b) at 30 m spatial resolution have been used to estimate glacier area change between the year 2000 and 2015. The summary of the data set is listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…This study refines the CD method for precise LU/LC pattern calculation (24). Study assesses optimal LU/LC mapping in Serdang, Selangor, Malaysia, comparing spatial resolutions (UAV, WorldView-2, Sentinel-2) with GS and Brovey algorithms for accuracy (25).…”
Section: Introductionmentioning
confidence: 98%